Famine as genocide? Ukraine and Ireland - Liam Kennedy (Queen's University Centre for Economic History (QUCEH), 2022)
The Great Irish Famine, 1846-50, and the Great Ukrainian Famine, 1932-33 are searing episodes in the history of the two countries. On some estimates, the relative intensity of famine in the two societies was broadly the same, with famine conditions claiming the lives of one-in-eight of the population. But on closer examination it is the dissimilarities between the two episodes that dominate. The politics and ideology shaping reaction to the emerging catastrophes in the two societies were hugely contrasting. The intent of policy in the Irish case, however inadequate some of the relief measures, was to save lives. Suspicion of the peasantry (not only in Ukraine), the extraction of grain surpluses and the unleashing of state terror against "class enemies" took precedence over saving lives in the Soviet handling of the Ukrainian famine. Paradoxically, it is the collective memory of famine and its politicisation that brings the Irish and Ukrainian calamities into closer relationship with each other.
Keywords: N43; N44; H53; N54; 330; Great Irish Famine (1846-50); Great Ukrainian Famine (1932-33)